Association between Prenatal One-Hour Glucose Challenge Test Values and Delivery Mode in Nondiabetic, Pregnant Black Women - Jerel M. Ezell; Rosalind M. Peters; Jessica E. Shill; Andrea E. Cassidy-Bushrow (Hindawi Limited, 2015)
Objective. We examined the association between 1-hour glucose challenge test (GCT) values and risk of caesarean section. Study Design. A prospective cohort study recruited 203 pregnant Black women to participate. At ~28 weeks of gestation, participants underwent a routine 1-hour 50 g GCT to screen for gestational diabetes mellitus. Logistic regression was used to examine the association between 1-hour GCT value and delivery mode. Results. Of the 158 participants included, 53 (33.5%) delivered via C-section; the majority (n=29; 54.7%) were nulliparous. Mean 1-hour GCT values were slightly, but not significantly, higher among women delivering via C-section; versus vaginally (107.8 ± 20.7 versus 102.4 ± 21.5 mg/dL, resp.; P=0.13). After stratifying by parity and adjusting for maternal age, previous C-section, and prepregnancy body mass index, 1-hour GCT value was significantly associated with increased risk of C-section among parous women (OR per 1 mg/dL increase in GCT value = 1.05; 95% CI OR: 1.00, 1.05; P=0.045). Conclusion. Even slightly elevated 1-hour 50 g GCT values may be associated with delivery mode among parous Black women.